Fine-Needle Pricking Test of the Parathyroid Gland during Thyroid Surgery in Predicting Parathyroid Function. (25th June 2022) - Wu, Ying-Jun; Wang, Jian-Biao; Li, Fei-Bo; Jin, Lei; Zhou, Liang; Xie, Lei
Abstract : Background . Permanent hypoparathyroidism is a serious complication following total thyroidectomy plus central neck dissection (CND). How to evaluate the vascularization of the parathyroid gland in real time is a major concern of thyroid surgeons. This study aimed to evaluate the fine-needle pricking (FNP) test in predicting parathyroid gland function. Methods . The FNP test was performed in patients undergoing total thyroidectomy plus CND between January 1, 2014, and December 31, 2019, to visualize the vascularization of the parathyroid glands. Patients were classified according to the number of parathyroid glands preserved in situ with excellent vascularity (PGPIEV) demonstrated by FNP: group 0 (without PGPIEV), group 1 (with one PGPIEV), group 2 (with two PGPIEV), group 3 (with three PGPIEV), and group 4 (with four PGPIEV). Results . A total of 608 patients with four parathyroid glands underwent FNP testing during thyroidectomy. At least one PGPIEV was demonstrated by FNP testing in 581 patients who had intact parathyroid hormone (iPTH) levels in the normal range after the operation. The prevalence of hypocalcemia decreased from 77.8% in group 0 to 9.8% in group 4 (P < 0.001 ), and the incidence of hypoparathyroidism decreased from 44.4% in group 0 to 0% in groups 1–4 (P < 0.001 ). iPTH concentrations on postoperative day 1 were positively correlated with PGPIEV groups (increased from 14.58 ng/l in group 0 to 45.22 ng/l in group 4, P < 0.001 ). Conclusions . The FNP test is a safe and reliable method to predict parathyroid function. One PGPIEV demonstrated by the FNP test rules out the possibility of patients developing hypoparathyroidism.